A chave do céu e a porta do inferno : os monges barbudos de Soledade e Sobradinho - Kopp, Maria da Glória Lopes (2014)
The movement of Bearded Monks (Monges Barbudos) of the Soledade and Sobradinho was compared by the Judge of the District of Candelaria with two other famous Braziliam rural movements: the muckers, which took place in Ferrabraz, Rio Grande do Sul; and Canudos, in Bahia. That Judge had acquitted the civilian and military for the murder of André Ferreira França, who died in August 1938, in the place known as Coloninha, Lagoão district, by that time the 6th district of Soledade. The protagonists of the Bearded Monks rural movement were rural farmers that advocated a kind of religiosity associated with practices of medicinal herbs, especially carob, and principles of peaceful community living, and appreciation of nature. They were mobilized around a thousand participants, endorsed by the prophet João Maria. During the Holy Week of 1938, two Police confrontations, with the cooperation of civilians, involved hundreds of people and left dead, wounded and more than one hundred prisoners. The two confrontations occurred in the Church of Santa Catarina, in Bela Vista district, and the Costa s Corner, in Jacuizinho district, both were district of Soledad. This monograph investigates unprecedented documents and interviews with the participants circa of 30 years after the event. In order to identify social, political and economic protagonists and opponents, the context of the 1930 s in Rio Grande do Sul and Brazil was established. A network of family relationships involving more than 40 families had been unveiled. The unifying core of that network was composed by Desiderius Fiuza, France and the Ferreira Gonçalves da Costa. In addition to these small holders, the movement mobilized remnants of Guaraní communities and ex-slaves that were living in the yerba mate and araucaria forest of the Middle Plateau and the Encosta da Serra regions. These rural workers were confronted by 500 opponents, among them municipal authorities, traders and merchants, farmers and settlers of foreign origin settlers in colonial settlement of the early 20th Century. The Bearded Monks resisted the economic and political crisis that took place before the WW II with the practicing of a mutual and mystical discourse. They were repressed and persecuted by the dictatorship of the Estado Novo (1937-1945).